S ANALISIS KINERJA SISTEM PENGENDALI KUALITAS AIR JARAK JAUH BERBASIS INTERNET OF THINGS - Josua Carmel Dopen Purba; Muhammad Rizki Syahputra; Beni Satria (CV. Hawari, 2026)
The use of water today is very large, many industries pollute the spring area, and household waste causes a decrease in water quality. The quality of the water used daily is not guaranteed. Then an automatic tool is needed to monitor water quality. This research is based on the Internet of Things using Arduino Uno as a microcontroller, Nodemcu ESP8266 as a wifi module, TDS sensor, LDR module and ds18b20 temperature sensor as a sensor. The design test used 3 different water samples under different conditions with a total of 30 sample tests. The research results are in the form of a tool that can monitor water quality. Based on the results of sample testing, the accuracy of the design in detecting water quality is 90%.